Digital assessment of real-world walking in people with impaired mobility: how many hours and days are needed? - Buekers, Joren; Chernova, Julia; Koch, Sarah; Marchena, José; Lemos, Jorge; Becker, Clemens; Bonci, Tecla; Braun, Julia; Brittain, Gavin; Buckley, Ellen; Caulfield, Brian; Del Din, Silvia; et al. (International journal of behavioral nutrition and physical activity, 2025)
Background: Impaired mobility increases falls and mortality risk. However, guidelines to reliably assess real-world walking activity and gait remain undefined. We aimed to (i) determine the minimum daily wear time during waking hours (7:00–22:00) for a valid measurement day, (ii) identify the minimum number of valid days, and (iii) weekend days, to reliably assess weekly walking activity and gait parameters, and (iv) provide recommendations for reliable real-world walking assessments. Methods: Participants with chronic obstructive pulmonary disease (n = 565), multiple sclerosis (n = 558), Parkinson’s disease (n = 543) or proximal femoral fracture (n = 487) from 10 countries were asked to wear a single wearable device on the lower back, 24 h/day for seven days, resulting in 13,191 measurement days. The Mobilise-D processing pipeline was used to obtain 24 daily walking activity and gait parameters. Minimum daily wear time was determined as the highest wear time category that did not statistically change parameter values. Intraclass correlation coefficients ≥ 0.80 determined the minimum number of valid measurement and weekend days. Results: The minimum daily wear time varied between “no requirement” (13% of parameter-condition combinations) and > 14 h (19%), with higher requirements for walking activity than gait parameters. The minimum number of days ranged from 1 (17%) to > 7 days (6%), and was higher for parameters that are yet to be clinically validated. There was no evidence of a weekend nor health condition effect on parameter reliability. Conclusions: For studies involving multiple walking activity and gait parameters or health conditions, expert consensus recommends a minimum of > 12 h of daily wear time across ≥ 3 days. For studies that involve specific parameters or health conditions, individual recommendations are provided within the manuscript.
Veröffentlicht: 21. November 2025
Gesehen am 30.01.2026